Classified characteristics of helium gas resources and controlling factors for the enrichment - Xinjun CHEN; Yi DING; Jingjing YI; Gang CHEN (Shiyou shiyan dizhi, 2023)
The lack of helium resources accounts for the limited helium supply in China. It is of great significance to classify of helium-enriched natural gas according to the characteristics of helium reservoirs and the main controlling factors of helium enrichment, thus the exploration and development of helium can be promoted and the safety of helium use in China may be ensured. Based on the origin of helium, this paper classifies the helium reservoirs by the consideration of the abundance of helium resources, the spatial horizon of uranium and thorium radioactive elements, the types of carrier gas reservoirs, and the main controlling factors of helium accumulation. The helium gas resources can be characterized into two types: crust-mantle mixed type and crust-source type. Crust-source type can be further classified into crust-source far-source type (including hydrocarbon associated type and water-soluble gas type) and crust-source near-source type (shale gas type) with different characteristics. In terms of helium reservoirs discovered in China, only crust-source helium which was formed together with hydrocarbon gas reservoirs has industrial utilization value due to the great resource potential, although its resource grade is relatively low. The main controlling factors of helium accumulation in the crust-source far-source type and crust-source near-source type are roughly the same, but there are differences in helium sources and migration pathways.